The Influence of On Time Delivery On Customer Satisfaction J & T (Jet & Tony) Drop Point Takalalla In Liliriaja Sub District Soppeng District - Dewi Fadillah; Aris Baharuddin; Sulmiah Sulmiah; Andi Muhammad Rivai (Public Resource Innovation Management and Excellence, 2024)
The Influence of On Time Delivery on Customer Satisfaction J&T Drop Point Takalalla in Liliriaja Sub District Soppeng District Thesis Business Administration Study Program. Faculty of Social Sciences and Law, Makassar State University Supervised by Aris Baharuddin and Sulmiah. This study aims to determine how much influence timeliness of delivery has on customer satisfaction at J&T Express Drop Point Takalalla in Liliriaja District, Soppeng Regency. This study used quantitative research with correlational methods with data collection techniques through observation and questionnaires. The sampling method used is purposive sampling. The data obtained from the research results were processed using SPSS version 22 which consisted of validity tests, reliability tests on research instruments and descriptive analysis techniques on the data obtained. The results show that the indicators used in each of these variables indicate that the effect of timeliness of delivery is in the good category, for indicators on the customer satisfaction variable are in the very good category. Based on the infrensial statistical analysis there is an influence between the two variables. So it can be concluded that there is a significant influence between on time delivery of customer satisfaction at J&T Express Drop Point Takalalla in Liliriaja District, Soppeng Regency.